Pengaruh Ansyitah (Aktiviti) Terhadap Pembentukan Akhlak Pelajar Sekolah Menengah Kebangsaan Agama (SMKA) (Sains Humanika, 2018)
This working paper is to look into the Ansyitah (activity) and its link to students’character Sekolah Menengah kebangsaan Agama (SMKA). This research in the form of observation is to find information on the Ansyitah (activity) used in SMKA. Feedback was obtained from questionnaires that were distributed to SMKA students. A total of 886 Form Four students from 5 zones namely East Zone, Central zone, South zone, North zones and East Malaysia zone were involued in the research. Students were required to respond to 13 items related to the Ansyitah (activity) strategy and 75 items on students’character in schools and boarding schools. The 5- points Likert Scale Response is used on the questionnaire. A descriptive statistic is used to report on the result of the research Ansyitah (activity) and the students’ character. The Spearman Correlation is used to explain the link between Ansyitah (activity) and the character of the SMKA students in schools and boarding schools. The finding of the result shows that the Ansyitah (activity) is at a high level (min=4.03,sp=0.679) and the character of the SMKA students in schools and boarding schools (min=4.22, sp=0.431). The analysis correlation shows significance between Ansyitah (activity)and the students character of the SMKA students in schools and boarding schools (r=0.496,p
Keywords: Ansyitah; students' character; SMKA; SMKA's students activities; moral formation.